Working alliance among mental health nurses in Indonesia: A comparative analysis of socio-demographic characteristics - Iyus Yosep; Henny Suzana Mediani; Linlin Lindayani (Belitung Nursing Journal, 2021)
Background: Working alliance between therapist and client in psychotherapy practice has become proven to compensate for a significant difference in various psychotherapy modalities. However, few studies have investigated the structure of alliance in the context of nurses working at mental health hospitals in Indonesia.  Objective: This study aimed to compare the working alliance of mental health nurses according to socio-demographic characteristics.  Methods: A cross-sectional research was performed at the Mental Health Hospital in West Java, Indonesia, as a referral hospital in Indonesia from May to December 2019. The inclusion criteria were nurses with a minimum of one year of working experience and a Diploma III certificate in nursing. Convenience sampling was used to recruit 120 nurses who agreed to join in this study. The working alliance was measured using Working Alliance Inventory-Short Revised-Therapist (WAI-SRT). Results: The majority of the respondents were female (77.5%), holding a Diploma III degree in nursing (49.17%), having working experience ranged from 11 to 15 years (34.17%), and working at the chronic unit (32.5%). The mean score of the working alliance was 44.46 (SD = 11.32). The domain of agreement on goals had a higher mean score (17.65 ± 3.45), followed by the task domain (16.56 ± 5.81) and bond domain (22.10 ± 7.23). There was a significant difference in working alliance according to education level and working experience (p < 0.05), while no significant differences in terms of gender and working unit. Conclusion: Mental health nurses with higher education levels and more vast working experience had higher working alliances. Thus, nurse managers and hospital policymakers should provide Continues Nursing Education (CNE), working alliance training, and therapeutic strategies for nurses to improve their working alliances. It is also essential to cooperate with nursing schools to include working alliances as learning objectives.